1. The Sensitivity Level Of Gentamicine, Cholramphenicol and Penicillin Inhibiting The Growth Of Pseudomonas Aeruginosa Bacteria Isolate From Aceh Bull Prepunce - Mada Admi; Annisa Anwar Sitorus; Rinidar Rinidar; Amalia Sutriana; Rosmaidar Rosmaidar; Sugito Sugito (Jurnal Medika Veterinaria, 2021)
This study aims to determine the sensitivity level of gentamicin, chloramphenicol and penicillin antibiotics to inhibit the bacterial growth of P. aeruginosa taken from preputium isolate of Aceh cattle. This Stock of Pseudomonas aeruginosa isolate from Microbiology Laboratory of FKH USK, re-identified its purity through: indole test, methyl red test, sugar test and as well as on Nutrient Broth (NB) media; incubated at 37ºC for 24 hours; observed the turbidity level of 0.5 Mc Farland solution. Then, the antibiotic sensitivity test was carried out using the method of Mueller Hinton Agar (MHA). The observations were made by measure the inhibition zone using the calipers in millimeters (mm) against antibiotics. The results of the observation of the inhibition zone on the gentamicin antibiotic was averaged of 25.5 mm, 23.7 mm chloramphenicol, and 12.1 mm penicillin. This study concluded that the gentamicin, chloramphenicol, and penicillin antibiotic were still effective against P. aeruginosa bacteria with the highest level of sensitivity seen in gentamicin antibiotic.